1991
DOI: 10.1023/a:1015861719134
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The inclusion complex formation of intravenously administered hydroxypropyl-beta-cyclodextrin and beta-cyclodextrin with endogenous lipids was studied. We tested the hypothesis that complex formation of endogenous cholesterol with cyclodextrins in the bloodstream leads to extraction of cholesterol from the large lipoprotein particles. The relatively small cholesterol-cyclodextrin complexes then leave the bloodstream via capillary pores, and dissociation of the complex in the extravascular compartment finally c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(43 citation statements)
references
References 15 publications
1
42
0
Order By: Relevance
“…Experimentally it is difficult to distinguish between the 2∶1 and 1∶1 complexes, and different methods predict binding constants varying over orders of magnitude. Keeping these limitations in mind, a comparison of the binding constants calculated from our PMFs predict an order of magnitude comparable to the experimental estimate [33], [34] for -CD and HP--CD, assuming the experiments probe the 2∶1 stoichiometry. In experiments on DM--CD [35], the binding affinity could be differentiated between the 2∶1 and 1∶1 stoichiometries; the 2∶1 case showed a much higher affinity in line with our results for -CD (See Text S1 for details)…”
Section: Resultssupporting
confidence: 64%
“…Experimentally it is difficult to distinguish between the 2∶1 and 1∶1 complexes, and different methods predict binding constants varying over orders of magnitude. Keeping these limitations in mind, a comparison of the binding constants calculated from our PMFs predict an order of magnitude comparable to the experimental estimate [33], [34] for -CD and HP--CD, assuming the experiments probe the 2∶1 stoichiometry. In experiments on DM--CD [35], the binding affinity could be differentiated between the 2∶1 and 1∶1 stoichiometries; the 2∶1 case showed a much higher affinity in line with our results for -CD (See Text S1 for details)…”
Section: Resultssupporting
confidence: 64%
“…However, the transmission electron microscopic visualization of the lipid matrix showed no changes in the organization of lipids in the intercellular spaces after treatment with aqueous solution of β-and γ-CyD, whereas treatment with hydroxypropyl-β-CyD produced significant change in the lamellar structure [25]. Frijlink et al [183] have reported formation of stable complexes with endogenous cholesterol in the bloodstream by hydroxypropyl-β-CyD. Similarly, Legendre et al reported the extraction of approximately 10% cholesterol and proteins by hydroxypropyl-β-CyD from the SC [182].…”
Section: Iv) Cyclodextrinmentioning
confidence: 99%
“…Using cyclodextrins to potentially remove agents such as cholesterol 54,57,114,115 and vitamin A 45,51,116,117 from the body have proven to be useful. These observations may imply that, since cyclodextrins are capable of removing unwanted agents from the body, they might also remove essential materials.…”
Section: Cyclodextrins and Site Of Administration Irritationsmentioning
confidence: 99%